Factors Driving Religious Conversion: A Case Study of Mualaf in Surabaya - Abdullah Abdullah (Lembaga Yasin AlSys, 2025)
This study investigates the underlying factors influencing religious conversion to Islam in Surabaya, employing a qualitative case study approach. Data were collected through in-depth interviews with individuals who had converted from various religious backgrounds, including Catholicism, Hinduism, Agnosticism, and one former Christian pastor, alongside leaders and members of the Mualaf Center Surabaya (Rumah Singgah Mualaf). The findings identify three primary pathways to conversion: (1) theological and intellectual exploration driven by doctrinal doubts or existential crises; (2) spiritual and mystical experiences, often involving dreams or emotional resonance with Islamic teachings; and (3) pragmatic and relational influences, including legal circumstances such as divorce, peer encouragement, and responses to social exclusion. These pathways reflect the complex interplay of cognitive, affective, and sociocultural dimensions in the conversion process. The study concludes that religious conversion is not a singular or linear event but a multifaceted and contextually embedded transformation shaped by intertwined personal and social catalysts.